2020
DOI: 10.1111/1744-9987.13462
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the circulatory effects of continuous renal replacement therapy using AN69ST and polysulfone membranes in septic shock patients: A retrospective observational study

Abstract: The acrylonitrile‐co‐methallyl sulfonate surface‐treated (AN69ST) membrane is expected to improve hemodynamics in patients with sepsis through cytokine adsorption. However, the clinical literature on AN69ST membranes is very limited. We aimed to compare the circulatory effects of continuous renal replacement therapy (CRRT) between patients using the AN69ST membrane and polysulfone (PS) membrane (a nonadsorbing membrane). This retrospective observational study enrolled 38 patients with septic shock, as defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Of these, 22 were excluded due to their focus on veno-arterial ECMO (V-A ECMO) or extracorporeal cardiopulmonary resuscitation (ECPR) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Fourteen studies were excluded for lack or scarcity of data on CytoSorb© use [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], four because of the lack of specific data for the ECMO subgroup [ 67 , 68 , 69 , 70 ], four because CytoSorb© was not used concomitantly with ECMO therapy [ 71 , 72 , 73 , 74 ], two because outcomes of interest for the simultaneous use of CytoSorb© and ECMO were not reported [ 75 , 76 ], and one because it focused on a different device [ 77 ]. One study was excluded because it only reported preliminary findings from other articles [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 22 were excluded due to their focus on veno-arterial ECMO (V-A ECMO) or extracorporeal cardiopulmonary resuscitation (ECPR) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Fourteen studies were excluded for lack or scarcity of data on CytoSorb© use [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], four because of the lack of specific data for the ECMO subgroup [ 67 , 68 , 69 , 70 ], four because CytoSorb© was not used concomitantly with ECMO therapy [ 71 , 72 , 73 , 74 ], two because outcomes of interest for the simultaneous use of CytoSorb© and ECMO were not reported [ 75 , 76 ], and one because it focused on a different device [ 77 ]. One study was excluded because it only reported preliminary findings from other articles [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some observational studies [33][34][35] have shown that AN69ST hemo lters are superior to non-AN69ST hemo lters. Furthermore, AN69ST and PMMA membranes have already been widely used in Japan [33][34][35][36][37], and no serious adverse events were observed in either group. Therefore, future RCTs are warranted to investigate the effect of AN69ST and PMMA hemo lters on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Some observational studies [ 33 35 ] have shown that AN69ST hemofilters are superior to non-AN69ST hemofilters. Furthermore, AN69ST and PMMA membranes have already been widely used in Japan [ 33 37 ], and no serious adverse events were observed in either group. Therefore, future RCTs are warranted to investigate the effect of AN69ST and PMMA hemofilters on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%